Subjective memory complaints in people with epilepsy: Are there “signature” complaints associated with anxiety and depression? - Cassandra Trend; Isha Puntambekar; Sallie Baxendale (Epilepsia Open)
Abstract Objective While there is a relatively weak association between cognitive complaints and performance on standardized tests of memory function, elevated levels of depression and anxiety are highly correlated with subjective memory complaints in people with epilepsy (PWE). The study examined whether there are “signature” constellations of memory complaints that are associated with anxiety and depression in PWE. If identified, these signatures may alert clinicians to the likelihood of mood playing a role when presented with these complaints in the neurology clinic. Methods Three hundred and seventy‐five adults with epilepsy, mean age 37 (s.d. 12.8), completed a Subjective Memory Questionnaire (SMQ), rating how often they experienced 19 different types of memory difficulty. Frequencies ranged from never to more than once a day on a six‐point scale. They also completed the Hospital Anxiety and Depression Scale. Results A principal component analysis of responses on the SMQ revealed three primary factors. Factor 1 comprised items primarily related to verbal memory lapses in social settings such as forgetting people's names, repetition and rambling in conversation, and difficulties following the thread of a discussion. Factor 2 comprised items related to losses from the core store of memories such as failure to recognize close relatives, getting lost, and forgetting autobiographical details. Factor 3 related to organizational/attentional aspects of memory with an executive component. People who reported moderate/severe levels of anxiety and depression on the HADS reported a higher frequency of memory failures in the social domain than those with no mood disturbance. Anxiety was associated with memory complaints mediated by executive functions, while depression was associated with increased reports of losses from the core memory store. Significance Anxiety and depression are associated with different subjective memory complaints in people with epilepsy. Paying attention to the nature of these complaints may help in the management of these difficulties. Plain Language Summary Anxiety and depression are associated with different patterns of memory complaints in people with epilepsy. In this study, we found that elevated levels of anxiety and depression are associated with memory complaints that impair social function. Anxiety is also associated with problems that have an executive basis, while depression is associated with reports of losses from the core memory store. Recognizing these patterns may help clinicians identify the most effective interventions for these difficulties.